(3GdhaG HeG jJYdb HHjY GdhaGs - (3eMeO Hf HjQe GdKGfjs
(3ChdgG (B:s
(3GdMeO ddg hcai agPg QSGdI ehSheI edNUI ef cJH KHJ dgG ai GdePgH GdMfai GdEUWaG eQJHI Ydi ebOeI hYTQI aUhd hNGJeI s
(3BNQgG (B:s
(3hajg TQW RGFO HNdGa GdQgf , aCZJfe gPG GdJMQjQ aEfg eaQO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs